. Equatorial Guinea – The personalist dictator toolkit for survival - Sanches, E.; Sá, Ana Lúcia (Presidential Power, 2021)
The rise of illiberal power and the persistence of authoritarian rule around the world has been one of the most disturbing trends of the past decades. Tiny Equatorial Guinea offers an illustrative example not only of the hallmarks of personalistic autocratic regimes, but also of the tools used by autocrats to survive. The country’s president, Teodoro Obiang Nguema Mbasogo, is the longest serving leader in Africa. Since seizing power through a coup d’état in 1979, he has used all means to hold onto power. In our most recent study we identify four essential strategies of regime survival: co-optation, restrictive institutional rules, repression, and international projection.